A survey on diversity herpetofauna species at delta Tumpat Mangrove Forest - Aniza Abd Talib (2018)
A rapid survey on diversity herpetofauna species at Delta Tumpat Mangrove Forest (DTMF) was carried out from 31th July to 31th August 2017. Amphibian (frogs and toads) and reptile (lizards) were either collected by pitfall trapping comprising terrestrial transect searching consisted active searching and direct observation while reptile (snakes) were collected by chance observation. All herpetofauna species were observed and identiﬁed. The result show 3 species of amphibians from 3 families and 8 species of reptiles from 7 families were present on DTMF. Of the amphibians, there were 2 species of ﬁogs and l species from toad. The most common toad species were Black-Spined Toad (Duttaphrynus melanostictus). Of the reptiles, there were 6 species of lizards, 2 species of snakes. The most commonly encountered reptiles were the Bell’s Butterﬂy Lizard (Leiolepis belliana) and Water Monitor Lizard (Varanus salvator) and Garden Lizard (Calotes versicolor). The number of amphibians and reptiles is lower because mainly due to short survey period, the nearness to the sea limits herpetofauna species at the location sites also to the secretive and elusive habits of these animals.